PENGARUH BUDAYA KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT PATRIA ANUGRAH SENTOSA PALEMBANG - Widya Gemilang; Endah Dewi Purnamasari; Shafiera Lazuarni (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
This study aims to determine and analyze the effect of work culture and compensation on employee performance at PT Patria Anugrah Sentosa Palembang, either partially or simultaneously. This study uses a quantitative approach by collecting data through survey methods. The data collection technique used in this study was a questionnaire with a Likert scale. The population in this study were employees at PT Patria Anugrah Sentosa, amounting to 32 people. The results of this study indicate that the value of t count is 2,249> t table 1,68 for work culture (X1) and t count is 10,426> t tabel 1,68 for compensation (X2). While the calculated f value is 173,064> f table 3,09. The results pf the analysis show that partially work culture and compensation each have a positive and significant effect on employee performance. And simultaneously, thet the variables of work culture and compensation together have a positive effect on employee performance, with R2 value of 92,3%.